Study of the Influence of Semi-Porous Baffles on the Three-Phase Separation Efficiency in a Horizontal Separator Vessel via CFD - Jessica B. da S. do Nascimento; Ferreira, Alysson D; Vasconcelos, Angela L U; Severino R. de Farias Neto (Journal of petroleum science and technology, 2024)
Horizontal separator vessels exhibit better phase separation efficiencies when fluids flow at lower velocities, favoring the sedimentation process. The optimized determination of internal devices, such as baffles, can reduce fluid velocity from the inlet to the separation region. This research aimed to evaluate the impact of semi-perforated baffles on flow dynamics and the separation efficiency of gas, oil, and water in a three-phase horizontal separator vessel. Moreover, to achieve this goal, a base geometry was adapted. Furthermore, two configurations of semi-perforated baffles were analyzed, varying their distance from the inlet, height relative to the vessel bottom, and vertical length. In addition, computational fluid dynamics was used to obtain numerical results. Moreover, the multiphase flow was modeled using the VOF method in conjunction with the standard k-epsilon turbulence model. Also, the results indicated that the insertion of baffles contributed to reducing the velocity of the inlet fluids. Ultimately, among the analyzed geometric arrangements, it can be concluded that the three-phase horizontal separator with a semi-perforated baffle at position P1 exhibited a more uniform three-phase flow and better liquid/gas (90.03%) and oil/water (100%) separation efficiencies when compared to the other studied geometries.